The Relationship Between Mastery of Concepts and Problems Solving Ability through the Problem Based Learning Model in Biology Subjects - Setiana, Anna; Suhendar, Suhendar; Widhikrama, Chandra; Azzura, Muhammad Nur (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2022)
Background: Activities that occur in the classroom during the Biology learning process are generally still teacher centered which places the teacher as the only source of information and only as a transfer of knowledge from teacher to student. This study aims to analyze the relationship between concept mastery and problem solving ability through problem-based learning model in Biology subject. The subjects in this study were students of SMA Negeri 4 Kota Sukabumi class XI IPA 3 with a total of 30 people in the even semester of the 2012/2013 academic year. Method: This study used correlational method with bivariate correlation research design. To capture aspects of students' concept mastery and problem-solving skills, instruments were used in the form of concept mastery tests and problem-solving skills tests in the form of multiple choice and student response questionnaires to the problem-based learning model to support the research results. Results: It can be seen from the results of testing the correlation Rhitung of 0.687> Rtabel (0.05) of 0.361 and the results of testing the significance of the correlation index Thitung of 7.217> Ttabel (0.05) of 2.048 with a coefficient of determination of 46.24. Conclusion: There is a positive and significant relationship between concept mastery and problem solving ability through problem-based learning model. Keywords : Concept Mastery; Problem Solving Ability; Problem Based Learning